Integrated Single-Cell Bioinformatics Analysis Reveals Intrinsic and Extrinsic Biological Characteristics of Hematopoietic Stem Cell Aging - Zeng, Xiangjun; Li, Xia; Shao, Mi; Xu, Yulin; Shan, Wei; Wei, Cong; Li, Xiaoqing; Wang, Limengmeng; Hu, Yongxian; Zhao, Yanmin; Qian, Pengxu; Huang, He (Frontiers in Genetics, 2021)
Hematopoietic stem cell (HSC) aging, which is accompanied by loss of self-renewal capacity, myeloid-biased differentiation and increased risks of hematopoietic malignancies, is an important focus in stem cell research. However, the mechanisms underlying HSC aging have not been fully elucidated. In the present study, we integrated 3 independent single-cell transcriptome datasets of HSCs together and identified Stat3 and Ifngr1 as two markers of apoptosis-biased and inflammatory aged HSCs. Besides, common differentially expressed genes (DEGs) between young and aged HSCs were identified and further validated by quantitative RT-PCR. Functional enrichment analysis revealed that these DEGs were predominantly involved in the cell cycle and the tumor necrosis factor (TNF) signaling pathway. We further found that the Skp2-induced signaling pathway (Skp2→Cip1→CycA/CDK2→DP-1) contributed to a rapid transition through G1 phase in aged HSCs. In addition, analysis of the extrinsic alterations on HSC aging revealed the increased expression levels of inflammatory genes in bone marrow microenvironment. Colony formation unit assays showed that inflammatory cytokines promoted cellular senescence and that blockade of inflammatory pathway markedly rejuvenated aged HSC functions and increased B cell output. Collectively, our study elucidated the biological characteristics of HSC aging, and the genes and pathways we identified could be potential biomarkers and targets for the identification and rejuvenation of aged HSCs.